PASTORAL COUNSELING FOR PARENTS OF CHILDREN WITH SPASTIC CEREBRAL PALSY - Suwito , Tri Prapto; Sembiring , Milisi (AGUSPATI Research Institute, 2024)
The level of difficulty faced by parents in a family is when there are one or two things that are very difficult for them to face for a long period of time and it is even uncertain how long the problem can be resolved. Parents will find a way with all their abilities and strengths to overcome this, or try to make it easier to overcome it, this is a problem related to the child they love. Sometimes the attitude of parents is all wrong because in addition to having to handle the child, it is also related to their good name and self-esteem, they also have to work hard to get the greatest income possible, the purpose of which is to take care of their child throughout the child's life from childhood to adulthood, this problem concerns the condition of children who have abnormalities or special needs called Spastic Cerebral Palsy, namely awkward reflexes, contractures (muscles or joints that are permanently tense), difficulty crawling and walking, stiff muscles in one or more parts of the body. The author conducted research with a qualitative descriptive approach, and from various sources of health knowledge, books and journals and their relationship to theology related to the problem, so that it will answer this problem and become a basis for Christians to respond correctly according to the teachings of the Word of God.